2021
DOI: 10.3390/rs13173355
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Potential of Sentinel-2 in Assessing the Drought

Abstract: This paper systematically reviews the potential of the Sentinel-2 (A and B) in assessing drought. Research findings, including the IPCC reports, highlighted the increasing trend in drought over the decades and the need for a better understanding and assessment of this phenomenon. Continuous monitoring of the Earth’s surface is an efficient method for predicting and identifying the early warnings of drought, which enables us to prepare and plan the mitigation procedures. Considering the spatial, temporal, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 207 publications
(274 reference statements)
0
11
0
Order By: Relevance
“…In this study, there are many three-band SRIs that combine the VIS, red-edge, and NIR wavelengths, and were effective for estimating the plant water status indicators and GY under different growth conditions. Interestingly, many studies have reported that there are several satellite-derived indices, especially those based on VIS/red-edge, NIR/VIS, and NIR/red-edge, that can achieve accurate estimation of different field measured agronomic traits, such as AGB [44,88], GY [89,90], and plant water status indicators [91,92]. Additionally, Herrmann et al [93] reported that the satellite-derived indices have been shown to provide almost comparable results as hyperspectral data.…”
Section: Application Of Hyperspectral Data For Simulated Satellite Datamentioning
confidence: 99%
“…In this study, there are many three-band SRIs that combine the VIS, red-edge, and NIR wavelengths, and were effective for estimating the plant water status indicators and GY under different growth conditions. Interestingly, many studies have reported that there are several satellite-derived indices, especially those based on VIS/red-edge, NIR/VIS, and NIR/red-edge, that can achieve accurate estimation of different field measured agronomic traits, such as AGB [44,88], GY [89,90], and plant water status indicators [91,92]. Additionally, Herrmann et al [93] reported that the satellite-derived indices have been shown to provide almost comparable results as hyperspectral data.…”
Section: Application Of Hyperspectral Data For Simulated Satellite Datamentioning
confidence: 99%
“…The selected indices were the MNDWI index with a threshold of −0.15 for Landsat-5 images, the MNDWI index and a threshold of −0.25 for Lansat-8 images, and the NDWI index and a threshold of −0.20 for Sentinel-2 images. These indices are among the most used for detecting water surfaces with both sensors, as they have a high ability to separate water zones from other coverages [6,14,18]. The NDWI index often identifies built-up areas as water.…”
Section: Discussionmentioning
confidence: 99%
“…The role of flooding extent and duration is crucial for biodiversity (wildlife habitat) and other wetland ecosystem services (e.g., carbon storage, water quality, storing, floodwater, and maintaining the water levels in the dry season) [6]. In ecology, historical trends and observation of long-term change is central to understanding [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely used satellites in PA and PV is the Sentinel-2 this satellite is capable of sampling 13 spectral bands up to a resolution of 10m. The main advantage of Sentinel-2 over other satellites is that the data are open-source [89]. The use of data derived from satellite platforms is very wide, examples include studies to identify vineyards growing in large regions or areas [90], monitor vineyard variability, predict yield variability [91].…”
Section: Satellitementioning
confidence: 99%